Scrofuloderma in a 1-year-old girl with severe malnutrition: a case report - Jasin, Madeleine Ramdhani; Neldy, Fahreza Aditya; Setyanto, Darmawan Budi; Nugroho, Gufron; Sunhaji, Valerie; Ham, Maria Francisca (Indonesian Pediatric Society, 2023)
Tuberculosis (TB) remains a global burden and a leading cause of mortality due to infectious diseases worldwide. In 2020, 845,000 new TB cases (312 per 100,000 population) were diagnosed, with 96,000 deaths, including 4,700 deaths of TB with HIV. Tuberculosis typically affects the lungs, but it can also affect other organs, a condition termed extrapulmonary TB. In 2020, 16% of all TB cases had extrapulmonary manifestations.1 The first case of TB affecting the skin was reported in 1826.2,3 There are many types of cutaneous TB; one of the most common is scrofuloderma, more often found in children and young adults.4 Scrofuloderma starts with a lesion in a lymph node, bone, muscle, or tendon that spreads to the skin.5 The lesion progresses very slowly and is usually not painful. Therefore, many patients wait to seek treatment until an advanced stage, leading to poor prognosis.3 In this report, we present a case of a severely malnourished one-year-old girl with scrofuloderma.